(3eONd UfGYI GdbQGQGJs - (3efjQ(B, (3TGcQ eMeOs ((3YeGf(B:s (3OGQ hGFd(B,s, 2005)
(3WHjYI GdJMdjd GdeGdj(B-(3COhGJ GdJMdjd GdeGdj(B-(3GdfSH GdYGdjI(B-(3JMdjd GdeQcR GdeGdj bUjQ GdCLd(B-(3JMdjd bGFeI GdJOabGJ GdfbOjI(B-(3GSJNOGe GdJMdjd GdeGdj aj GdJfHD HGdaTd GdeGdj(B-(3JMdjd JMdjd YdGbGJ GdJcdaI(B-(3GdMLe(B-(3GdQHM(B-(3JMdjd caGAI GdYed hOQLI GdQGaYI(B-(3JMdjd GdeQcR GdeGdj Whjd GdCLd hJcdaI GdJehjd(B.s
Keywords: (3GdJMdjd GdeGdjs